2003
DOI: 10.1136/bjsm.37.3.239
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of running injuries: the Vancouver Sun Run “In Training” clinics

Abstract: Objectives: Seventeen running training clinics were investigated to determine the number of injuries that occur in a running programme designed to minimise the injury rate for athletes training for a 10 km race. The relative contributions of factors associated with injury were also reported. Methods: A total of 844 primarily recreational runners were surveyed in three trials on the 4th, 8th, and 12th week of the 13 week programme of the "In Training" running clinics. Participants were classified as injured if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
294
1
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(348 citation statements)
references
References 20 publications
(24 reference statements)
23
294
1
26
Order By: Relevance
“…In our trial, severity (ie, restriction of running) and a minimal duration of 1 week was added. If our definition was changed in to the definition used by Taunton et al, 24 the number of RRIs would be 34.3 per 100 runners at riskhigher than in the Vancouver Sun Run study.…”
Section: Buist Et Almentioning
confidence: 99%
See 3 more Smart Citations
“…In our trial, severity (ie, restriction of running) and a minimal duration of 1 week was added. If our definition was changed in to the definition used by Taunton et al, 24 the number of RRIs would be 34.3 per 100 runners at riskhigher than in the Vancouver Sun Run study.…”
Section: Buist Et Almentioning
confidence: 99%
“…In conjunction with the positive effects of running on health and fitness, it is important to consider the risk of a running-related injury (RRI). Research has shown that the incidence of RRI is high; incidence rates of RRI vary from 30% to 79%, 3,[11][12][13][14]24,28 and from 7 to 59 RRIs per 1000 hours of running. 3,11,12,19 Most RRIs are overuse injuries of the lower extremity.…”
Section: Copyrightmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite this, runners are also known to be highly susceptible to chronic injuries [2], with an incidence rate of around 70% over the course of one year [3]. A number of intrinsic and extrinsic risk factors have been associated with the aetiology of running injuries, such as mileage, previous injury, number of years of training, training characteristics, running mechanics, surface and footwear [4].…”
Section: Introductionmentioning
confidence: 99%